2012
DOI: 10.1208/s12249-011-9724-9
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synergistic Galactomannan-Based Unit Dosage Form for Sustained Release of Acarbose

Abstract: Abstract. In the current study, the potential of a novel combination of a galactomannan with acarbose (100 mg) was evaluated for attaining a desired hypoglycaemic effect over a prolonged period of time. Three major antidiabetic galactomannans viz., fenugreek gum, boswellia gum, and locust bean gum were selected in order to achieve a synergistic effect in the treatment alongwith retardation in drug release. In vitro studies indicated that batches containing various proportions of fenugreek gum (AF40-60) were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
2
6
0
1
Order By: Relevance
“…Moreover, Nayak et al also reported that hydrophilic FSM also binds with water to form viscous gel-structure, which barricades the pores on the surface of polymeric matrix [76] . Retardation of drug release from polymer matrix might be the synergistic effect of both viscosity and gel forming properties of FSM, which also corroborated with various earlier findings [48,[77][78][79] .…”
Section: Able 2: Percent Weight Loss Of 5-fu Sa Fsm Pm Dpm and Bfsupporting
confidence: 90%
“…Moreover, Nayak et al also reported that hydrophilic FSM also binds with water to form viscous gel-structure, which barricades the pores on the surface of polymeric matrix [76] . Retardation of drug release from polymer matrix might be the synergistic effect of both viscosity and gel forming properties of FSM, which also corroborated with various earlier findings [48,[77][78][79] .…”
Section: Able 2: Percent Weight Loss Of 5-fu Sa Fsm Pm Dpm and Bfsupporting
confidence: 90%
“…The hypoglycemic effect of Fenugreek seed powder discussed in our study is well supported by few studies [ 9 , 11 , 24 , 25 ] which showed hypoglycemic effect in both type 1 and type 2 diabetes subjects. In vivo study by Kumar RV et al [ 26 ] depicted a significant reduction ( p < 0.001) in the postprandial blood glucose levels in the diabetic rats on treatment with Fenugreek formulation AF40.…”
Section: Discussionmentioning
confidence: 99%
“…Further to confirm structural changes in the protein with acarbose, the UV-visible spectra were also measured with different concentrations. Figure 2 shows the UV-visible spectra of the different protein-drug complexes where the absorption intensity decreased with increasing concentration with a slight blue shift in the spectrum [1,32 ]. These observed spectra revealed that the interaction between acarbose and proteins changed the structure of proteins.…”
Section: Calculationsmentioning
confidence: 99%
“…Acarbose is a type of noninsulinotropic oral antidiabetic drug molecule, which mainly used to treat type two diabetes [1]. It is mainly used with a proper diet supplemented food and regular exercise to control the blood sugar in humans [2].…”
Section: Introductionmentioning
confidence: 99%